Stargazer [compact disc, unabridged] - Carman, Patrick (Carman, Patrick. Land of Elyon (Audio), 2008)
After a tragic attack by an evil force, Alexa and her friend Yipes are stranded in a strange community known as the Five Pillars. Each pillar of rock has its own secrets--and its own challenges. As darkness descends, Alexa must risk everything to defeat it--even if it means taking to the skies.